2020
DOI: 10.36713/epra5808
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Credit Access Among Smallholder Dairy Farmers in Kinangop Sub-County, Kenya

Abstract: Dairy farming plays a major role in the Kenyan agricultural sector as it is dominated by smallholder farmers who contribute approximately 80 per cent of the total milk production. In Kinangop Sub County, there are many credit service providers however, not all smallholder dairy farmers have benefited from such services, instead smallholder dairy farmers have continued to experience challenges such as limited access to financial services. This study therefore analyzed the determinants of credit access among sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
6
3
0
Order By: Relevance
“…In line with previous studies (Assogba et al, 2017;Ongwech et al, 2020), higher educational levels increased the likelihood of rice farmers having access to loans in this study. This is probably because farming households with more education are likely to have better knowledge of farming techniques, investments, and business management, which might (1) enhance the capacity to manage high levels of agricultural production (Alhassan et al, 2020), (2) increase asset accumulation, thereby reducing the effects of inadequate collateral (Adejoh and Adah, 2018), and (3) facilitate access to (paid) extension services that may be needed to accompany the farmer in successfully implementing larger agricultural investments after loan acquisition (Maniriho et al, 2021).…”
Section: Determinants Of Access To Agricultural Creditsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies (Assogba et al, 2017;Ongwech et al, 2020), higher educational levels increased the likelihood of rice farmers having access to loans in this study. This is probably because farming households with more education are likely to have better knowledge of farming techniques, investments, and business management, which might (1) enhance the capacity to manage high levels of agricultural production (Alhassan et al, 2020), (2) increase asset accumulation, thereby reducing the effects of inadequate collateral (Adejoh and Adah, 2018), and (3) facilitate access to (paid) extension services that may be needed to accompany the farmer in successfully implementing larger agricultural investments after loan acquisition (Maniriho et al, 2021).…”
Section: Determinants Of Access To Agricultural Creditsupporting
confidence: 92%
“…Based on these results, the study recommended policies supporting the expansion of formal and semi-formal financial credit portfolios that embrace cocoa farmers, deriving alternative funding opportunities that put less emphasis on collaterals on a reduced interest rate as central to improving credit access, and reducing poverty among cocoa farmers in the Ahafo Region of Ghana. Ongwech et al (2020) examined the determinants of credit access in Kinangop Sub County, where despite the presence of many credit service providers, many smallholder dairy farmers still experienced limited access to financial services. Applying a binary logistic regression analysis on data from 230 dairy farmers, it was observed that marital status, years of schooling, savings frequency, occupation, financial education, association membership, and numbers of dairy cattle were significant credit access determinants.…”
Section: Review Of the Determinants Of Microcredit Accessmentioning
confidence: 99%
“…The average age did not vary significantly (p = 0.0119) between the credit adopters and non-adopters. The findings align with those of [17], who reported that the average age of dairy farmers, credit borrowers, and non-borrowers ranged between 41 and 50 years. The study revealed an average schooling of 12 years, mostly focused on secondary education for dairy cattle farmers, indicating a reasonable formal education level (Table 2).…”
Section: Descriptive Statisticssupporting
confidence: 89%
“…Agricultural credit plays a role in modernizing agriculture, improving input flow, and enhancing production efficiency. Similarly, [17] noted that credit access accelerates agricultural modernization and contributes to economic development by facilitating optimal input use. [26] further highlighted that credit access enhances production efficiency among small-scale farmers, reducing rural poverty and food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, financial training enables farmers to develop proper plans and make informed decisions concerning credit use and return maximization. Similar findings were reported by Wadeya et al (2020), who indicated that access to financial training significantly influenced credit use.…”
Section: Determinants Of Rural Farm Household Participation In the Se...supporting
confidence: 87%